Effects of Polysaccharide Elicitors on Secondary Metabolite Production and Antioxidant Response in Hypericum perforatum L. Shoot Cultures - Sonja Gadzovska Simic; Oliver Tusevski; Stéphane Maury; Alain Delaunay; Claude Joseph; Daniel Hagège (The Scientific World Journal)
The effects of polysaccharide elicitors such as chitin, pectin, and dextran on the production of phenylpropanoids (phenolics and flavonoids) and naphtodianthrones (hypericin and pseudohypericin) in Hypericum perforatum shoot cultures were studied. Nonenzymatic antioxidant properties (NEAOP) and peroxidase (POD) activity were also observed in shoot extracts. The activities of phenylalanine ammonia lyase (PAL) and chalcone-flavanone isomerase (CHFI) were monitored to estimate channeling in phenylpropanoid/flavonoid pathways of elicited shoot cultures. A significant suppression of the production of total phenolics and flavonoids was observed in elicited shoots from day 14 to day 21 of postelicitation. This inhibition of phenylpropanoid production was probably due to the decrease in CHFI activity in elicited shoots. Pectin and dextran promoted accumulation of naphtodianthrones, particularly pseudohypericin, within 21 days of postelicitation. The enhanced accumulation of naphtodianthrones was positively correlated with an increase of PAL activity in elicited shoots. All tested elicitors induced NEAOP at day 7, while chitin and pectin showed increase in POD activity within the entire period of postelicitation. The POD activity was in significantly positive correlation with flavonoid and hypericin contents, suggesting a strong perturbation of the cell redox system and activation of defense responses in polysaccharide-elicited H. perforatum shoot cultures.